1975
DOI: 10.1152/jn.1975.38.5.1037
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of superior olivary neurons to binaural stimuli

Abstract: This investigation was undertaken to study the timing properties of low-frequency binaural neurons located in the medulla of kangaroo rat (Dipodomys spectabilis). The results show that the response variables, vector strength (VS) and discharge rate (DR), are not necessarily related responses; each may be conveying a different parameter of acoustic stimuli. The results also lead to the conclusion that binaural low-frequency neurons, whether they are excitatory-excitatory (EE) or excitatory-inhibitory (EI), in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

1979
1979
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 0 publications
1
27
1
Order By: Relevance
“…Previous physiological studies have generally supported the idea that MSO neurons act as coincidence detectors (Batra et al 1997b;Crow et al 1978;Goldberg and Brown 1969;Grothe and Sanes 1994;Joris 1996;Moushegian et al 1975;Spitzer and Semple 1995;Yin and Chan 1990). These studies have amply demonstrated that the ITD eliciting maximal discharge is equal to the delay in response to stimulation of either ear.…”
Section: Discussionmentioning
confidence: 80%
“…Previous physiological studies have generally supported the idea that MSO neurons act as coincidence detectors (Batra et al 1997b;Crow et al 1978;Goldberg and Brown 1969;Grothe and Sanes 1994;Joris 1996;Moushegian et al 1975;Spitzer and Semple 1995;Yin and Chan 1990). These studies have amply demonstrated that the ITD eliciting maximal discharge is equal to the delay in response to stimulation of either ear.…”
Section: Discussionmentioning
confidence: 80%
“…The medial superior olivary complex is the first nucleus on the ascending auditory pathway to receive bilateral inputs and thus represent binaural auditory processing (Moushegian et al, 1975). It has been shown that when the crossing fibers of the trapezoid body are lesioned in the brainstem there is a loss of BI in the brainstem potentials (Buchwald and Huang, 1975;Fullerton and Hosford, 1979;Gardi and Berlin, 1981;Levine et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Interaural time differences (ITDs) are the dominant cue for localizing low-frequency sounds, which are most important for larger mammals (including humans) and small mammals living in habitats that require detection of distant sounds and longrange communication (like Mongolian gerbils). These species have well developed low-frequency hearing and a well developed medial superior olive (MSO) with principal neurons highly sensitive to ITDs (Goldberg and Brown, 1969;Moushegian et al, 1975;Crow et al, 1978;Yin and Chan, 1990;Spitzer and Semple, 1995).…”
Section: Introductionmentioning
confidence: 99%